Computer System Implementation on Teacher Performance in Elementary Schools - Abdul Sakti; Aminah Djunaid (Journal of Engineering, Electrical and Informatics, 2025)
This study analyzes the impact of computer system implementation on teacher performance in elementary schools using a qualitative approach. Data were collected through in-depth interviews with 15 teachers, participatory observation, and analysis of school policy documents. The findings indicate that computer systems enhance administrative efficiency and foster collaboration among teachers, although challenges such as technological competency gaps and limited infrastructure persist. The study identifies three main themes: time optimization, improved data accuracy, and the dynamics of technological adaptation. These findings highlight the need for ongoing training and infrastructure support to maximize the benefits of computer systems in primary education environments.